2021
DOI: 10.3389/fvets.2021.603775
|View full text |Cite
|
Sign up to set email alerts
|

Agreement of Magnetic Resonance Imaging With Computed Tomography in the Assessment for Acute Skull Fractures in a Canine and Feline Cadaver Model

Abstract: Computed tomography (CT) is the imaging modality of choice to evaluate patients with acute head trauma. However, magnetic resonance imaging (MRI) may be chosen in select cases. The objectives of this study were to evaluate the agreement of MRI with CT in the assessment for presence or absence of acute skull fractures in a canine and feline cadaver model, compare seven different MRI sequences (T1-W, T2-W, T2-FLAIR, PD-W, T2*-W, “SPACE” and “VIBE”), and determine agreement of four different MRI readers with CT d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
(44 reference statements)
2
6
0
Order By: Relevance
“…It also con rmed a higher accuracy and interobserver repeatability of VIBE studies compared to T2W-TSE for correct classi cation of caudal articular processes. This is consistent with previous ndings in assessment of other small animal bony changes, such as Hecht et al (11) who found a 93.9% agreement of skull fracture identi cation with VIBE to CT this shows also transferrable use of MRI in looking at bone morphology. Our ndings suggest that VIBE sequences could potentially be considered in place of CT to identify CAP abnormalities.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It also con rmed a higher accuracy and interobserver repeatability of VIBE studies compared to T2W-TSE for correct classi cation of caudal articular processes. This is consistent with previous ndings in assessment of other small animal bony changes, such as Hecht et al (11) who found a 93.9% agreement of skull fracture identi cation with VIBE to CT this shows also transferrable use of MRI in looking at bone morphology. Our ndings suggest that VIBE sequences could potentially be considered in place of CT to identify CAP abnormalities.…”
Section: Discussionsupporting
confidence: 92%
“…Volumetric interpolated breath-hold examination (VIBE) is a form of volumetric imaging using fast 3D gradient-echo sequences that produces T 1 images and was rst introduced by Rofsky in 1999 (6) It has the advantage of improving Z-axis resolution, which makes it possible to obtain high-quality multiplanar and 3D reconstruction images. VIBE has been effectively used in breast (7), human abdominal (8) and musculoskeletal imaging (9) with use in veterinary medicine limited for assessing facial neuritis (10) and skull fractures (11). Hecht et al (11) found VIBE imaging was highly accurate in identifying post mortem skull fractures in animals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CT is generally considered the gold standard in the evaluation of acute traumatic head injury. MRI has been shown to have fairly high accuracy in fracture in identification in a canine and feline cadaver model ( 50 ). However, both the brain and cervical spine were imaged in this patient, and only a limited number of sequences and planes were acquired to minimize time under general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of history for five of the dogs prevents a more exhaustive establishment of a relationship between a possible traumatic event and MRI findings. All the studies were lacking proton density weighted sequences, which are considered the most useful sequences for detecting bone traumatic lesions ( 30 ). In addition, the quality of the MRIs obtained with a low field unit could limit the recognition of subtle signs of head trauma, causing one to underestimate the real number of presumed acquired traumatic cases.…”
Section: Discussionmentioning
confidence: 99%